Relevance of nerve conduction velocity in the assessment of balance performance in older adults with diabetes mellitus. Issue 5 (27th February 2017) - Wang, Ting-Yun; Chen, Shih-Ching; Peng, Chih-Wei; Kang, Chun-Wei; Chen, Yu-Luen; Chen, Chun-Lung; Chou, Yi-Lin; Lai, Chien-Hung
Abstract: Purpose This study investigated the relationship between peripheral nerve conduction velocity (NCV) and balance performance in older adults with diabetes.Methods Twenty older adults with diabetes were recruited to evaluate the NCV of their lower limbs and balance performance. The balance assessments comprised the timed up and go (TUG) test, Berg balance scale (BBS), unipedal stance test (UST), multidirectional reach test (MDRT), maximum step length (MSL) test and quiet standing with eyes open and closed. The relationship between NCV and balance performance was evaluated by Pearson's correlation coefficients, and the balance performances of the diabetic patients with and without peripheral neuropathy were compared by using Mann–Whitney U tests.Results The NCV in the lower limbs exhibited a moderate to strong correlation with most of the balance tests including the TUG ( r  = −0.435 to −0.520, p  < 0.05), BBS ( r  = 0.406–0.554, p  < 0.05), UST ( r  = 0.409–0.647, p  < 0.05) and MSL (r = 0.399–0.585, P  < 0.05). In addition, patients with diabetic peripheral neuropathy had a poorer TUG ( p  < 0.05), BBS ( p  < 0.01), UST ( p  < 0.05) and MSL performance ( p  < 0.05) compared with those without peripheral neuropathy ( p  < 0.05).Conclusion Our findings revealed that a decline in peripheral nerve conduction in the lower limb is not only an indication of nerve dysfunction, but may also be related to the impairment of balance performance in patients with diabetes. Implications for Rehabilitation: Nerve conduction velocity in the lower limbs of diabetic older adults showed moderate to strong correlations with most of the results of balance tests, which are commonly used in clinics. Decline in nerve conduction velocity of the lower limbs may be related to the impairment of balance control in patients with diabetes. Diabetic older adults with peripheral neuropathy exhibited greater postural instability than those without peripheral neuropathy.